Comparative effectiveness of surgery versus external beam radiation with/without brachytherapy in high‐risk localized prostate cancer. (7th November 2019) - Yin, Ming; Zhao, Jing; Monk, Paul; Martin, Douglas; Folefac, Edmund; Joshi, Monika; Jin, Ning; Mortazavi, Amir; Verschraegen, Claire; Clinton, Steven
Abstract: Background: It remains controversial if radical prostatectomy or definitive radiation therapy produces equivalent outcomes in high‐risk localized prostate cancer. Methods: We queried The Surveillance, Epidemiology, and End Results (SEER) database for those who received upfront surgery or who were recommended for surgery but instead received radiation. Inverse probability of treatment weighing was used to adjust for covariate imbalance and the weighted Cox proportional hazards model was used to estimate the effects of treatment groups on survival. A meta‐analysis was performed to pool estimates from published studies. Results: Among eligible 62 533 patients, 59 540 had upfront surgery and 2993 patients had upfront radiotherapy. EBRT + BT was associated with a superior cancer‐specific survival (CSS) compared with surgery or EBRT alone (HR, 0.55, 95% CI, 0.3‐1.0; HR, 0.49, 95% CI, 0.24‐0.98, respectively), whereas EBRT was associated with an inferior overall survival (OS) compared with surgery (HR, 1.46, 95% CI, 1.16‐1.8). Radiotherapy (EBRT ± BT) was inferior to surgery by OS (HR, 1.63, 95% CI, 1.13‐2.34) in patients ≤ 65 years, and was superior to surgery by CSS in patients > 65 years (HR, 0.69, 95% CI, 0.49‐0.97). The meta‐analysis showed consistent results. Conclusion: EBRT + BT was associated with a significantly better prostate CSS compared with surgery or EBRT. EBRT alone was inferior to surgery by OS. Abstract : In high‐risk localized prostate cancer, radiotherapy with brachytherapy boost was associated with a longer survival outcome, compared with surgery or radiotherapy without brachytherapy boost.